Oyster Aquaculture Empowerment: Penguatan Teknis Budidaya dan Kelembagaan Kelompok Petani Tiram di Desa Kartika Jaya - Satsya Yoga Baswara; Yozi Aulia Rahman; Pipit Ayu Lestari; Hasna Zatil Aqmar; Fathia Auliya Khairunnisa; M. Surya Hidayatullah; Bayu Fajar Setyawan; Shelomitha Azalia Widiyaningrum; Wahyu Luthfiyana Sari; Syifa Wafirah; Reyhansha Agna Fasha; Shafira Nabila Anjarsari; Nayla Zhulfa; Aisyah Amalia Putri; Tri Apriyono; Ghazy Ammar Andrian; Dewi Ramadhani; Firza Ferdiansyah; Indriyani Indriyani (Yayasan Kawanad, 2026)
Kartika Jaya Village, Patebon Subdistrict, Kendal Regency, has abundant oyster resources, but their utilization remains suboptimal due to the absence of a structured cultivation system and weak farmer group institutions. This community service activity aimed to examine the process and outcomes of strengthening the cultivation capacity and institutional capacity of the Oyster Farmer Group in Kartika Jaya Village through the Oyster Aquaculture Empowerment program. The program consisted of socialization, technical cultivation training, field mentoring, development of an oyster cultivation module, and institutional strengthening. A qualitative descriptive-analytical approach was used, supported by data from interviews, observations, documentation, and pretest-posttest assessments involving 10 partner members. The results showed an increase in participants' understanding of oyster cultivation techniques, with the mean score increasing from 59.00 in the pretest to 79.50 in the posttest. The training was also followed by the direct application of cultivation techniques through the installation of four cultivation cages and continued field mentoring. The activity produced an oyster cultivation module and supported the formalization of the farmer group through member deliberation. These technical and institutional outcomes provide a basis for the continued development of oyster cultivation activities and future improvement of farmers' economic benefits. Further mentoring is recommended, particularly in product marketing, post-harvest development, and access to business capital.